Disparities in awareness and treatment among women with hypertension: Insights from the American Heart Association Research Goes Red Registry - Megan M. McLaughlin; Alexis L. Beatty (Elsevier, 2024)
Hypertension is an important modifiable risk factor for cardiovascular disease and affects nearly one-third of women in the U.S. Prior research has demonstrated declining rates of blood pressure (BP) control nationally among women, and there are significant racial and ethnic disparities in both hypertension prevalence and outcomes among U.S. women. However, national-level data on attitudes and awareness of women with hypertension are limited. To address this gap, data were analyzed from participants with self-reported hypertension enrolled in the American Heart Association's Research Goes Red Registry. Of 6170 women who responded as of February 2023, 1835 (30 %) reported a history of hypertension. The top health concerns reported among women with hypertension were weight, healthcare access and costs, and hypertension. Health concerns varied significantly by age, race, and ethnicity; younger women and Black and Hispanic women were more likely to report hypertension as their top concern. Among women with self-reported hypertension, 77 % reported knowing their BP, and 90 % reported being on an anti-hypertensive. Black and Hispanic women were less likely to know their BP compared to White women. Younger women were less likely to be treated for hypertension, and there were also disparities in treatment by employment status and among uninsured women. In this national registry of women in the U.S., gaps and disparities exist in awareness and treatment of hypertension, highlighting targets for quality improvement in hypertension care for women.